Implementation of Minimax with Alpha-Beta Pruning as Computer Player in Congklak - Brian Sumali; Ivan Michael Siregar; Rosalina Rosalina (Maranatha University Press, 2016)
Congklak is one of the most popular traditional board games in Indonesia. It is said to train mathematical aspect of the player. Interestingly, nowadays more and more people are becoming less interested. Nowadays, people are paying less attention to traditional things and instead focus more to digital and electronic devices, including Indonesian. Traditional things are beginning to be forgotten from the minds of Indonesian. To re-capture Indonesianâ€™s heart for traditional things, one of the ways is to digitize them. Hopefully by making a video game of Congklak more people, especially Indonesian, become more interested in Congklak as one of Indonesian traditional. Minimax Algorithm with its improvement, Alpha-Beta pruning is an option to make an intelligent computer player for Congklak. By applying Minimax Algorithm to the computer player, it becomes intelligent enough to play Congklak as a good opponent; making the game more fun.Keywordsâ€” congklak, minimax algorithm, alpha-beta pruning, artificial intelligenceÂ